Ice cream passion fruit flavored elaborated with green banana biomass and sucralose - Aragão, Daisy de Macedo; Araújo, Yvna Farias Vieira; Carvalho, Emanuella Abrantes da Silva; Gusmão, Rennan Pereira de; Gusmão, Thaisa Abrantes Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Ice cream is a great source of energy. Among the most consumed food in the world, it has fat and sugar as main ingredients in its composition. Due the seek for healthier food, the food industry has been driven to formulate new products that offer quality together with a good nutritional value. The present work aims to develop ice cream formulations replacing the vegetable fat hydrogenated by green banana biomass, and sugar (sucrose) by sweetener sucralose. With the prepared ice creams, we carried out the physical analyzes (texture, melting, color and ° Brix) and physical-chemical (moisture ph, acidity, lipids, sugars total, reducing sugars and ash). The values obtained for the analysis of moisture, ph, acidity and ash were consistent with the legislation for formulations analyzed. Regarding the melting test, the ice cream prepared showed good resistance. In the texture and overrum analysis, samples that replaced the vegetable fat by biomass banana Green and sucrose by sucralose were the ones that required the bigger strength to extrusion (parameters texture high) and also obtained largest incorporation of air (overrum). Between the differences, it can be noted that the use of banana Green biomass intervenes significantly in the contents of lipids of the ice cream as well as its structural arrangement. The results found for analysis of lipids were three times smaller for formulations that used green banana biomass as a substitute fat hydrogenated, which proves the nutritional benefits of pulp. Finally, the formulation that used sucralose as a substitute sucrose got final value of total sugars and reducing sugars lower compared to the default formulation.